UJI KONSENTRASI IAA (INDOLE ACETIC ACID) DAN BA (BENZYLADENINE) PADA MULTIPLIKASI PISANG VARIETAS BARANGAN SECARA IN VITRO - Ricky Indri Hapsari; Astutik Astutik (Universitas Tribhuwana Tunggadewi, 2009)
A study that was aimed to determine the effects of IAA and BA concentrations on number of shoot at multiplication phase of barangan banana, was conducted at Plant Tissue Culture Laboratory of Tribhuwana Tunggadewi University from October 2007 to January 2008. Treatment combinations of three levels of IAA, i.e. 0,0 mg/l; 0,15 mg/l and 0,30 mg/l, and three levels of BA, i.e. 4,0 mg/l; 4,5 mg/l and 5,0 mg, were arranged in a completely randomized design with three replicates. Results of this study indicated that there was interaction effect of IAA and BA to shoot variable at 6, 8, 10 and 12 weeks after sub culture application. Combination of concentration IAA 0,0 mg/l and BA 4,0 mg/l (I0 B1) achieved highest shoot number. But there was no significant effect of I0B2 and I1B3 treatments. The fastest shoot growth was observed for application of BA 4,0 mg/l, and BA 4,5 mg/l